Analisa Pengembangan Karir Aparatur Sipil Negara pada Dinas Kependudukan dan Pencatatan Sipil Kota Bima - Nur Annisa (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2022)
This study aims to analyze the career development of state civil apparatus at the population and civil registration office of Bima city. This research uses a qualitative method with a descriptive qualitative approach. From this research the results obtained that: 1) The State Civil Apparatus has Education and competence in accordance with the position it is engaged in, it has also been determined that the Educational qualifications in each part of the work that is occupied. 2) The most important training is to develop knowledge about methods and strategies to serve the community and training using technology to improve the ability of employees to face the times. There is limited funding to conduct training, so it is not possible to conduct training every year. Therefore, the central government needs to hold training to support employee abilities, because the transfer of knowledge from the central government is certainly better and can make all employees more enthusiastic in improving their work abilities. 3) The State Civil Apparatus in the disdukcapil is ready to accept the mutation decision issued by the mayor of Bima, because the mayor of Bima has the absolute right to transfer employees within the Bima city government.